EFFECT OF DISSOLVED NUTRIENT CONCENTRATION (NITRATE AND ORTHOPHOSPHATE) ON ABUNDANCE OF CHLOROPHYTA IN PENJALIN RESERVOIR BREBES REGENCY - Novi Ariyanti; Carmudi Carmudi; Christiani Christiani (UNEJ e-Proceeding, 2016)
This study aimed to find out the concentration of nitrate and orthophosphate in Penjalin Reservoir’s water, to find out community structure (abundance, diversity and dominance) of Chlorophyta in Penjalin Reservoir’s water and to confirm the effect of nitrate and orthophosphate concentration on Chlorophyta’s abundance in Penjalin Reservoir’s water. Survey method was performed at 6 station namely the center, the inlet and the outlet. Sampling was done 3 times with 4 weeks interval each. Water quality was analysed descriptively based on the criteria of quality standard in PP No. 82 tahun 2001 class III. The abundace of Chlorophyta was counted with volumetic method. The diversity was analysed with Shanon-Wienner’s diversity index, while the dominance was analysed with Simpson’s dominance index. The effect of nitrate and orthophosphate concentration on Chlorophyta’s abundance was confirmed with correlation and regression analysis. Nitrate concentration was 0.348 mg.l-1 - 0.568 mg.l-1. Orthophosphate concentration was 0.006 mg.l-1 – 0.075 mg.l-1. Chlorophyta’s abundance was 2.418 – 6.955 ind.l-1 with Tetraedron minimum as the most abundant species. Diversity index (H′) value was 2,08 – 2,75 and dominance index (C) value was 0,08 – 0,21. The effect of nitrate and orthophosphate concentration on Chlorophyta’s abundance was strong proven by correlation coefficient (r) value at 0,797 and determination coefficient value at 0,635 (63,50%). The regression equation was Y = 42,14 + 145 Nitrate + 1.280 Orthophosphate.